Influence of Multiwall Carbon Nanotube on Polyethersulfone/ Polyvinyl Alcohol Blend Membranes - Iqbal, Ahmed; Nur Farahah, Mohd Khairuddin; Ani, Idris; Noordin, Mohamed Yusof (Penerbit Universiti Teknologi Malaysia, 2014)
This paper investigates the influence of multiwall carbon nanotube (MWCNT) on the morphology and properties of polyethersulfone (PES) and polyvinyl alcohol (PVA) blend membranes. Several membranes were prepared by blending 0.5 wt% MWCNT , 18%wt PES and 1.5wt% PVA of various molecular weights (60, 145 and 200 kDa) in dimethyl acetate (DMAC) solvent. The membranes were then evaluated in terms of its morphology, contact angle, water flux rate and porosity. The results revealed that MWCNT nanoparticles have decreased the contact angle and increased the flux rate of PES/PVA blend membranes. The presence of MWCNT in the PES/PVA membranes have promoted the formation of fingerlike pores in the membranes structure and thus increased the porosity of the membranes. Besides that, the use of higher molecular weight PVA helped to reduce the contact angle of the membranes reflecting to their hydrophilic nature. However, the use of lower molecular weight PVA was found to enhance the increased of flux rate and porosity of the membrane.